Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2016)
A dataset containing 1763 species occurrences available in GBIF matching the query: { "and" : [ "Country is Spain", { "or" : [ "TaxonKey is Potamogeton praelongus Wulfen", "TaxonKey is Potentilla grandiflora L.", "TaxonKey is Prenanthes pendula subsp. flaccida Svent.", "TaxonKey is Primula lofthousei Hesl.-Harr.", "TaxonKey is Primula pedemontana Gaudin", "TaxonKey is Prunus lusitanica L.", "TaxonKey is Pseudomisopates rivas-martinezii (Sánchez Mata) Güemes", "TaxonKey is Pseudoscabiosa grosii (Font Quer) Devesa", "TaxonKey is Psilotum nudum (L.) P.Beauv.", "TaxonKey is Pteris incompleta Cav.", "TaxonKey is Ptilostemon casabonae (L.) Greuter", "TaxonKey is Puccinellia fasciculata var. fasciculata", "TaxonKey is Puccinellia pungens (Pau) Paunero", "TaxonKey is Pulicaria burchardii subsp. burchardii", "TaxonKey is Pulicaria canariensis var. canariensis", "TaxonKey is Pulicaria canariensis subsp. lanata Bramwell & G.Kunkel", "TaxonKey is Pulicaria crispa (Forssk.) Benth. ex Oliv.", "TaxonKey is Quercus ×alpestris Boiss.", "TaxonKey is Quercus pauciradiata Penas, Llamas, Pérez Morales & Acedo", "TaxonKey is Ranunculus alnetorum W.Koch", "TaxonKey is Ranunculus bupleuroides subsp. bupleuroides", "TaxonKey is Ranunculus bupleuroides subsp. cherubicus J.A.Sánchez Rodr., M.J.Elías & M.A.Martín", "TaxonKey is Ranunculus carlittensis (Sennen) Grau", "TaxonKey is Ranunculus envalirensis Grau", "TaxonKey is Ranunculus lingua L." ] } ] } The dataset includes 1763 records from 69 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0007404-160623103540712/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences